Assessment of human activities on soil contamination in Egypt: implications for the MENA region - Hendawy, Ehab; Belal, Abdel-Aziz; Sheta, Abd El Aziz S.; Mohamed, Elsayed Said; Kucher, Dmitry E.; Jalhoum, Mohamed E. M.; Shokr, Mohamed S.; Ali, Abdelraouf M.; Othman, Yahia A.; Abou-Hadid, Ayman F. (Frontiers in Environmental Science, 2025)
IntroductionDecision-makers around the world are very concerned about contaminated soil since it has a direct effect on soil and food security. This study seeks to evaluate soil contamination by a chosen heavy metal, Ni, Mn, Co, Cu, Cd, Pb, Fe, and Zn in the studied area located around the Kitchener drain in Egypt, its main source for irrigation water in the studied area and it extends 69 km and pass through Gharbia, Kafr El-Sheikh and Dakahlia Governorates, Egypt near).MethodologyPrincipal component analysis (PCA), cluster analysis, contamination factor (CF) and degree of contamination (DC) indices, which Quantified the level of contamination hazard supported by GIS, were used to determine the level of soil contamination in the area under study.ResultsThe spatial pattern of studied variables by kriging shows that The K-Bessel model is fitted for electrical conductivity (EC), Ni, and Cu, the exponential model is well-suited for pH, CaCO3%, and Fe in the soil, and the circular model fit for Mn. Stable model for silt, furthermore, a Gaussian model was fitted for Sand, Clay, and Cd and the hole Effect model for Co. As these models had low Mean Standardized Error (MSE) values (around zero) and Root-Mean-Square Standardized Error (RMSSE) values that were close to one. It indicates that the modals’ forecasts are roughly as precise as the baseline. The study area was divided into three zones based on the unconventional results of the integration of PCA and cluster analysis; each zone has a different heavy metal concentration and pattern. The results showed, that 0.82% of the studied area, the pollution was at a moderate level. Very high levels of heavy metal contamination were found throughout most of the area (79.24%); average concentrations of these metals were found to be 132.2+/-31.8,672.6 ± 125.4, 8.9 ± 5.1,103.8 ± 44.4, 25.5 ± 3.5,30.6 ± 10.3,223,021.4 ± 40484, and 246.5 ± 248.7 mg kg−1 for Ni, Mn, Co, Cu, Cd, Pb, Fe, and Zn, respectively. On the other hand, 19.92% of the studied area is contaminated considerably. There are various sources of contamination; such as household goods and industrial trash, including those from the textile, paint, sewage, and leather tanning industries; agricultural wastes, particularly those that contain pesticides and superphosphate fertilisers; and sewage sludge.ConclusionOverall mapping soil contamination could help decision-makers create suitable heavy metal mitigation strategies. To lessen human harmful behaviors that create environmental contamination, the study suggests enacting farm management legislation. Future research will also concentrate on strategies for controlling and lessening the consequences of soil pollution.